The determinants of Party System Change in Sub-Saharan Africa - Riccardo Pelizzo (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
This article examines what socio-economic factors are conducive to changes in the patterns of inter-party competition in Sub-Saharan Africa (SSA). The literature has in recent years paid considerable attention to measuring party system change, to identifying the consequences of party system instability for the proper functioning of democratic regimes, and to understanding what factors are responsible for the instability of party systems. In contrast to previous studies that view political change in general and party system change more specifically as the result of social transformation, development, modernization and change in the cleavage structure, this paper shows instead that poverty is the primary driver of party system change in the SSA region. In countries with high levels of poverty, political elites do enjoy little to no performance-based legitimacy. The lack of performance-based legitimacy is the reason why voters in such countries are willing to alter their voting habits and parties are unable to preserve their electoral fortunes over time—which is precisely why party systems do change. The literature showed that stable party systems are good for democracy. This paper shows that to enhance the stability of party system in SSA, poverty has to be reduced and possibly eradicated.